Pottery craft and culture - Randell, Gillian (Rhodes University, Faculty of Humanities, Department of Fine Art, 1972)
"The idea and fact of containment have been the primary significance of pottery from the beginning, and pots of all ages and peoples, even when their ostensible function was ceremonial or symbolical, have expressed by their generous swelling volumes, the potential or holding things of vital importance to man food, liquid or the furnishings of the grave." The utilitarian value of a pot is inseparable from its aesthetic quality. "There can be no fullness of complete realization or utility without beauty, refinement and charm, for the simple reason that their absence must in the long run be intolerable to both maker and consumer... The continued production of utilities without delight in making and using is bound to produce only boredom and to end in sterility." Modern pottery, whether industrial or that of the artist potter, has each in its different way tended to separate the aesthetic and the utilitarian. This is one symptom of the cultural decline of our Western tradition since the Eighteenth Century. The making of pots has persisted from earliest times to the present day through our ever changing world. Circumstances have at times obscured the essential truths of this art.
Keywords: Pottery craft